2006
DOI: 10.1002/app.24864
|View full text |Cite
|
Sign up to set email alerts
|

Effect of organosilica isomers on the interfacial interaction in polyimide/aromatic organosilica hybrids

Abstract: ABSTRACT:We report the effect of organosilica precursor isomers on the interfacial interaction between polyimide and organosilica in polyimide/organosilica hybrid composite films. Poly(4,4 0 -oxydianiline biphenyltetracarboxamic acid) (BPDA-ODA PAA) was used as the polyimide precursor, while the organosilica was made using o-substituted, m-substituted, and p-substituted phenyl organosilica precursor isomers. For the preparation of precursor hybrid films, BPDA-ODA PAA and organosilica precursors were mixed and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…The only detectable structural difference between these two polyimides is the presence of P aOF in only the ODPA material. This trend is expected based on the lack of structural features seen in previously studied fluorinated polyimides and possible aromatic interaction and order generally seen in nonfluorinated polyimides . Both systems show shoulders that are essentially identical in size and are similar in size to PEG domains found in previously studied PEG–imide systems .…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…The only detectable structural difference between these two polyimides is the presence of P aOF in only the ODPA material. This trend is expected based on the lack of structural features seen in previously studied fluorinated polyimides and possible aromatic interaction and order generally seen in nonfluorinated polyimides . Both systems show shoulders that are essentially identical in size and are similar in size to PEG domains found in previously studied PEG–imide systems .…”
Section: Resultssupporting
confidence: 59%
“…The more bulky fluorinated dianhydride is expected to have more free volume and more mobility than the ether‐containing dianhydride based on previous work studying polyimides . The additional free volume and mobility could lead to a higher possible ionic liquid uptake.…”
Section: Resultsmentioning
confidence: 98%
“…The imide-active silica therefore was found to be a better reinforcement for PIs then the pure silica, obtained from TEOS, as higher thermal stability and mechanical strength and improved transparency were observed. The effect of organo-silica isomers on the interfacial interaction in polyimide/ aromatic organo-silica hybrids has also been studied by Choi et al [30]. The 29 Si NMR of the polyimide/organo-silica hybrid films showed that organo-silica limits the perfect sol-gel reaction because of the steric hindrance effect of the substituted moieties.…”
Section: Introductionmentioning
confidence: 95%
“…65 Specifically, it is likely that the substituted benzenes may contribute to the intensity of these two peaks. 66 The spectrum for H-SOMS shows the high temperature treatment to have a significant impact on the chemical structure of SOMS. The appearance of peak around -105 ppm region indicates (SiO) 4 -Si* at which Si* is linked to four SiO groups.…”
Section: Si Nmrmentioning
confidence: 98%